The Spanish Baroque and Latin American Literary Modernity Writing in Constellation. - Chemris, Crystal Anne (Monografías A Ser., 2021)
This book aims to develop a broader view of the trajectory of Hispanic modernity, tracing a motif of recurring impasse, first seen in peninsular Baroque texts and continuing into Latin American colonial and modern literature.